Parental Attention and Learning Motivation Contribution to Career Planning of Vocational School Students - Atikah Rahmah Nasution; A Muri Yusuf (Universitas Negeri Padang, 2021)
Ideally, vocational high schools are able to produce graduates who can immediately enter the world of work. However, the reality is that there are still vocational high school graduate students who are still unemployed after graduating, this is because students do not prepare career plans beforehand. This type of research is quantitative with a correlational descriptive approach. The sample in this study amounted to 32 vocational students who were determined using purposive sampling. The instrument used was a parental attention questionnaire, a learning motivation questionnaire and a student career planning questionnaire. In addition, researchers also used a Likert scale model instrument. The analysis technique used is simple regression and multiple regression. The research results found that; 1) parental attention contributes significantly to student career planning, 2) learning motivation contributes significantly to student career planning, and 3) parental attention and learning motivation together contribute significantly to student career planning.